Ugotavljanje prostega formaldehida v lesnih tvorivih - Gornik Bučar, Dominika (Zbornik gozdarstva in lesarstva, 2000)
The quantity of free formaldehyde in wood products in spite of low values is still the subject of constant supervision and also the subject of new investigations. Despite numerous methods developed and in use, there is, presently, still no universal method by means by which the quantity of free formaldehyde release in wood products can be established with certainty. In the various countries, various standardised methods are in use. The correlations among some of them are still unknown. In the article we determined the content of released free formaldehyde in particleboards according to the perforator method with the objective to determine the correlation between the iodimetric titration and acetylacetone method. Becausethe quantity of released formaldehyde is also affected by the structureof the material, we also tried to establish the influence of the composition of a chipboard on the quantity of released formaldehyde. The correlation between the iodimetric titration and acetylacetone method is good (R2 = 0.8265). The composition of a chipboard (where we limited ourselves to the ratio between the middle and external layers of the particleboard) has influence on the quantity of released formaldehyde.
Keywords: analizne metode; formaldehid; lesni proizvodi; sledljivost